Pengaruh Tekanan Ketaatan Pada Audit Judgment Dengan Religiusitas Sebagai Variabel Pemoderasi - Surya, Luh Putu Lusi Setyandarini; Dewi, Cok Istri Ratna Sari (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p14, 2019)
Obedience pressure is one of the factors that can influence audit judgment. This compliance pressure arises due to the expectation gap that occurs between the entity examined and the auditor that has caused conflict for the auditor. Previous research suggest that obedience pressure is not consistently affecting audit judgment. The aim of this research is to gather empirical evidence of the effect of obedience pressure on audit judgment with religiosity as moderating variables. The sample for this research is taken with census sampling method. The data were collected by using questionnaire, given to 65 auditors who work at Public Accountant Firm all over the Province of Bali. The data were analysed using Simple Linier Regression and Moderated Regression Analysis (MRA). The result showed that obedience pressure is negatively affecting audit judgment and religiosity is able to moderate the effect of obedience pressure on audit judgment.   Keywords : Obedience Pressure; Audit Judgment; Religiosity.